Early referral to nephrological care improves long-term survival and hospitalization after dialysis initiation, independent of optimal dialysis start – a call for harmonization of reimbursement policies - Mathias Haarhaus; Lavinia O. Bratescu; Nicolae Pana; Emanuela M. Gemene; Eliana M. Silva; Carla Alexandra R. Santos Araujo; Fernando Macario (Renal Failure)
Early treatment of kidney disease can slow disease progression and reduce the increased risk of mortality associated with end-stage kidney disease. However, uncertainty exists whether early referral (ER) to nephrological care per se or an optimal dialysis start impacts patient outcome after dialysis initiation. We determined the effect of ER and suboptimal dialysis start on the 3-year mortality and hospitalizations after dialysis initiation. Between January 2015 and July 2018, 349 patients with ≥1 month of follow-up started dialysis at nine Romanian dialysis clinics. After excluding patients with COVID-19 during follow-up, 254 patients (97 ER and 157 late referral) were included in this retrospective study. The observational period was truncated at 3 years, death, or loss to follow-up. Clinical and laboratory data were retrieved from the quality database of the nephrological care providers. Patients were followed for a median (25–75%) of 36 (16–36) months. At dialysis start, ER patients had higher hemoglobin, phosphate, and albumin levels and started dialysis less often via a central dialysis catheter (p < 0.001 for each). Logistic regression analysis demonstrated an independent lower risk for frequent hospitalizations for ER patients (odds ratio 0.22 (95% confidence interval 0.1–0.485), p < 0.001), and Cox regression analysis revealed an improved survival (hazard ratio 0.540 (95% confidence interval 0.325–0.899), p = 0.02), both independent of optimal dialysis start. In conclusion, early referral to nephrological care was associated with improved survival and lower hospitalization rates during the three years after dialysis initiation, independent of optimal dialysis start. These results strongly support the reimbursement of nephrological care before dialysis initiation.